Counselling Learning Disabled Students - Wetherly, Robin (Canadian Journal of Counselling and Psychotherapy, 2011)
Learning Disabled students have specific counselling needs which can be effectively met through practical techniques. The literature on LD has tended to focus upon identification and remediation. This article describes the nature of the required counselling as well as the techniques that a wide variety of authors have found to be effective.